Peningkatan Karakter dan Motivasi Belajar Melalui Teladan Guru Madrasah Diniyah Nurul Muttaqin Desa Tegalrejo Kecamatan Pulung - Vivia Salma Azzahro; Mariana Mariana (Social Science Academic, 2025)
This study aims to describe the analysis of increasing the characteristics and motivation of students learning through the role of the teacher in Madrasah Diniyah in Tegalrejo Village Pulung Subdistrict Ponorogo District. Education is verry important for nation to increase its competitiveness in accordance with political, economic, cultural law and defense in a globalized world society, even developed countrues continue to develop their education. Teachers are an important part of education and learning. The teachers and student activities are create a reciprocal relationship between teachers and and students during learning. Improving the quality of teachers in learning is one of the efforts to improve the quality of education. The role of the teacher in the learning process is to act as an inspirer,, information provider, motivator, unifier, facilitator, guide and also evaluator. Objects and data are sourced from madin students in Tegalrejo village, Pulung sub-district, Ponorogo district. While the method chosen is the method of interviews and observations. Because the object under study was a madin student in Tegalrejo village, Pulung sub-district, Ponorogo district. While the data analysis technique used is a qualitative research technique